2016
DOI: 10.1038/mp.2016.160
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal bone morphogenetic protein signaling mediates behavioral effects of antidepressant treatment

Abstract: Many antidepressants stimulate adult hippocampal neurogenesis, but the mechanisms by which they increase neurogenesis and modulate behavior are incompletely understood. Here we show that hippocampal bone morphogenetic protein (BMP) signaling is modulated by antidepressant treatment, and that the changes in BMP signaling mediate effects of antidepressant treatment on neural progenitor cell proliferation and behavior. Treatment with the selective serotonin reuptake inhibitor fluoxetine suppressed BMP signaling i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 65 publications
4
32
0
Order By: Relevance
“…Notably, the direction of effect in these gene sets changed between P14 and adulthood – at P14, gene sets related to proliferation and differentiation were enriched with elevated expression in bLRs, whereas by adulthood elevated expression was seen in bHRs. This pattern fits the changing role of Bmp4 across development: Bmp4 is important for neural induction during early development (102, 103), but later suppresses neurogenesis (100, 104106) and promotes other cell fates (102, 107). For example, Bmp4 can a promote endothelial proliferation (84), which matches the elevated endothelial-specific gene expression that we observed in the bLR hippocampus at P14.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Notably, the direction of effect in these gene sets changed between P14 and adulthood – at P14, gene sets related to proliferation and differentiation were enriched with elevated expression in bLRs, whereas by adulthood elevated expression was seen in bHRs. This pattern fits the changing role of Bmp4 across development: Bmp4 is important for neural induction during early development (102, 103), but later suppresses neurogenesis (100, 104106) and promotes other cell fates (102, 107). For example, Bmp4 can a promote endothelial proliferation (84), which matches the elevated endothelial-specific gene expression that we observed in the bLR hippocampus at P14.…”
Section: Discussionsupporting
confidence: 69%
“…These results are consistent with the association between Bmp4 and anxiety and depressive-like behaviors in the literature. Blocking Bmp4 expression in mice reduces anxiety and depressive-like behavior and increases the effectiveness of certain anti-depressant treatments (100). Similarly, transgenic mice that are deficient for Bmp receptors have extremely low levels of anxiety and diminished fear conditioning (101).…”
Section: Discussionmentioning
confidence: 99%
“…These NSCs undergo cell division, and some daughter cells differentiate into functional neurons that participate in learning and memory and general cognition through integration into pre‐existing neural networks (de Miranda, Zhang, Katsumoto, & Teixeira, ). Further evidence suggest that it is the dorsal hippocampus that is involved in spatial learning and memory, while the ventral hippocampus is more associated with limbic functions (Brooker, Gobeske, Chen, Peng, & Kessler, ; Hyer, Hunter, Katakam, Wolz, & Glasper, ; Kheirbek & Hen, ; Loxton & Canales, ; McHugh, Fillenz, Lowry, Rawlins, & Bannerman, ; Schoenfeld, McCausland, Sonti, & Cameron, ). Abnormalities in hippocampal function are associated with various neurological and psychiatric disorders in adults such as anxiety, schizophrenia and depression (Ampuero, Jury, Hartel, Marzolo, & Zundert, ; Brooker et al, ; Caruncho et al, ; Danzer, Kotloski, Walter, Hughes, & McNamara, ; Liu et al, ; Perez‐Domper et al, ; Yun et al, ).…”
Section: Locations Of Adult Neural Stem Cells In the Mammalian Brainmentioning
confidence: 99%
“…Studies have demonstrated that decreased neurogenesis may be one cause of depression (Tamura et al, ). Indeed, many antidepressants have been shown to stimulate adult hippocampal neurogenesis (Brooker et al, ). It has been proposed that different sub‐regions of the hippocampus may regulate the distinct functions associated with the hippocampus (Bettio et al, ).…”
Section: Functional Aspects Of New Dgcs In the Adult Hippocampusmentioning
confidence: 99%
See 1 more Smart Citation